2023
DOI: 10.1038/s41467-022-35431-x
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy with immune checkpoint blockade, antiangiogenesis, and chemotherapy for locally advanced gastric cancer

Abstract: Despite neoadjuvant/conversion chemotherapy, the prognosis of cT4a/bN+ gastric cancer is poor. Immune checkpoint inhibitors (ICIs) and antiangiogenic agents have shown activity in late-stage gastric cancer, but their efficacy in the neoadjuvant/conversion setting is unclear. In this single-armed, phase II, exploratory trial (NCT03878472), we evaluate the efficacy of a combination of ICI (camrelizumab), antiangiogenesis (apatinib), and chemotherapy (S-1 ± oxaliplatin) for neoadjuvant/conversion treatment of cT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 85 publications
(97 reference statements)
2
66
0
Order By: Relevance
“…1). We defined the ORR as pCR (no residual tumor cells in the resected specimens and all resected lymph nodes) + major pathological response (≤ 10% viable tumor cells in the resected primary tumor and all resected lymph nodes) + partial pathological response (≤ 50% viable tumor cells in the resected primary tumor and all resected lymph nodes) 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…1). We defined the ORR as pCR (no residual tumor cells in the resected specimens and all resected lymph nodes) + major pathological response (≤ 10% viable tumor cells in the resected primary tumor and all resected lymph nodes) + partial pathological response (≤ 50% viable tumor cells in the resected primary tumor and all resected lymph nodes) 15,16 .…”
Section: Methodsmentioning
confidence: 99%
“…29 Several previous studies have shown that LAGC/GEJC patients with positive PD-L1 have a higher chance of achieving pCR, but no definite conclusion can be drawn because of lack of randomized phase III studies, and potential bias may occur due to our small sample size. 24,30,31 There are several limitations exist in our study: Firstly, our study is a single-arm study without a control group; secondly, the patients in our study were recruited from a single-center and the number was limited, which may cause potential bias; thirdly, the follow-up of EFS and OS is still ongoing and the data are immature at present, further results are warranted to analyze survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…In the EPOC1706 study, combination of pembrolizumab and lenvatinib resulted in a 69% ORR as first-or second-line treatment in 29 advanced or metastatic G/GEJ adenocarcinoma cases (13). Recently, there were several preliminary explorations about the application of anti-PD-1 agent plus anti-angiogenic drug and chemotherapy in second-line (14) and pre-operative (15) therapy of advanced GC. A phase 2, single-arm, prospective study assessed the efficacy and safety of the combination therapy of camrelizumab, apatinib, and S-1 in patients with G/GEJ adenocarcinoma as second-line treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Complete and major pathological response (pCR and MPR) rates were 15.8% and 26.3%, respectively. Grade 3 or higher adverse events occurred in 2 out of 25 patients (15). Although these studies have explored the application of immunotherapy plus antiangiogenic drugs and chemotherapy in treating advanced or metastatic GC, and indicated its efficacy and safety in…”
Section: Introductionmentioning
confidence: 99%